Mind the dad-A review on the biopsychosocial influences of drug abuse on father-infant interaction - Jovin Jie Ning Lee; Ilaria Cataldo; Aurora Coppola; Ornella Corazza; Gianluca Esposito (Elsevier, 2021)
Substance use disorder (SUD) is an issue of concern that can have inter- generational impacts. Fathers affected by this disorder can exhibit atypical parenting that leaves pronounced, adverse consequences for the child, espe cially during a critical window for development, such as neonatal life and infancy. However, factors sustaining paternal drug use and its associated health outcomes remain elusive. The present review provides a systematic literature search of the scientific evidence published until February 2021 on PubMed Central, Scopus, PsycInfo, and PubMed databases. Adopting a biopsychosocial model, this review provides comprehensive insights into the issue, detailing: (i) the neurobiological correlates of paternal substance use and atypical parenting mechanisms, (ii) influence of drug consumption on paternal psychological state, and (iii) the social environment modulating the social dynamics central to fathers with SUD. Attention is also paid to the bidirectional relationships between paternal drug abuse and fatherhood, which has been severely neglected so far. Findings shed new light on the importance of paternal contributions to the father-child interaction, supporting the formulation of more targeted multidisciplinary interventions aimed at restoring such a crucial and overlooked relationship.